A Review of Landslide Risk and Proactive Measures in Uttarkashi District, Uttarakhand (India) - Poonam Kainthura, Neelam Sharma (International Journal of Advanced Science and Technology, 2020)
Uttarkashi district of Uttarakhand state is located in hilly regions surrounded by many small and big rivers. Many tourists are attracted to this region due to adventurous activities and pilgrimage. Landslide is a common phenomenon in the Uttarkashi district that is natural and anthropogenic. This leads to damage to infrastructure, utilities, services, economy, and most important life which incurred huge expenditures investigations and mitigation and prevention strategies to control the damage. This paper aims to discuss a)the major landslides occurred in the district, b)study of probable causative factors that t increases the risk of landslides and triggers landslides, c)measures already taken to control the damage and d) introduce the latest decision making machine learning techniques for fast and proactive actions. The study will be useful to analyze and understand landslides, the risk level of landslides, and identification of most influencing triggering factors that causes landslides. In addition to this use of machine learning techniques would help in revealing hidden combinations of causative factors and prediction of future landslides. The implementation may benefit government authorities and officials of risk, mitigation, and management team.